An analysis of pulling motions in the crawl arm stroke - Belokovsky, V. V. (First International Symposium on "Biomechanics and Swimming, Waterpolo and Diving", 14-16 September 1970. Proceedings, 1971)
This study was undertaken to investigate the pulling motions of the arms during the sprint crawl stroke. The most of specialists analysing the pattern of arm motions in crawl don't use date of apparat methods exc1using some works of the last years (2,3,4,5). In our study we intended to classify different types of pressure against the palms of swimmers in the crawl arm stroke.